A study on thermal (conductivity and resistivity) properties of corn husk and coconut coir fibers as alternative cellulosic fibrous materials for dry wall board - Federizo, Nezcel Mae B.; Olalo, Kristin Faye M. (2018)
Waste materials contribute harmful effects in the environment thus it is essential to efficiently utilize these and make it be valuable. In this research, agri-waste/bio-waste, specifically fibers that were extracted from com husk and coconut coir, were considered in production of drywall boards. The research was conducted in order determine its performance as an additive cellulosic material for dry wall boards. The study focused on exploring its thermal properties and other physical properties such as absorption (moisture and water), and fire-resistance.Five formulations (A, B, C, D, and E) based on plaster (Plaster of Paris) -binder (Perlite)-fiber ratio using percentage by weight were used in the study. During testing, each formulation exhibited the following R-values: A (0.33ft.h.°F/Btu), B (0.30 ft.h.°F/Btu), C (0.46 ft.h. F/Btu), D (0.64 ft².h.°F/Btu), and E (0.55 ft.h.°F/Btu). It was evident that formulation D (70% plaster of Paris, 15% perlite powder, 15% coconut coir) exhibited significant result among the five formulations. Also even when compared with commercially available building. In terms of moisture and water absorptivity, the BWDB Formulation samples exhibited poor results. Only formulation samples A, B, D, and E showed an accepted absorption rate value that is equal to or not greater than (s) 5%. Moreover, with respect to the accepted building board standards, all formulation samples showed insignificant results on water absorption rate exceeding the accepted absorption rate of 10 to 45. In terms of resistance to fire, BWDB formulation samples were not fire resistant but may be considered as fire retardant.With the result of research findings, the material can be applied in residential condominiums as interior partitions (walls and ceilings). Besides providing thermal comfort to users and residents, it would promote sustainability and waste optimization. For further researches, it is recommended to use advanced technology to obtain more reliable results. Also, calculating the production cost and possible saleable price (for standard size) of the produced new material and comparing it to those commercially available drywall boards is highly recommend.
Thesis (BS Architecture)-- University of the Philippines Mindanao, 2018